ADAPTASI MASYARAKAT TERHADAP BENCANA BANJIR DI KECAMATAN BARUS KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - sihotang, mona tasya (JURNAL BUANA, 2026)
This research aims to determine: 1) Characteristics of flood areas. 2) Forms of community adaptation to flood disasters in Barus District. The type of research is descriptive quantitative. There were 100 respondents. The instrument used in the research was filling out a questionnaire. The results of this research are: 1) The dominant slope in the 0-8% Flat class is 13.50 km2, the dominant soil texture percentage is sandy loam and throughout the year the area receives high rainfall, reaching 2,998.1 mm/year. The lowest rainfall fell in August, namely 122.8 mm/month and the highest rainfall in January, namely 436.9 mm/month. The average rain is 226 days/year and the air temperature is 26.90C-28.20C. 2) Forms of physical adaptation include building a house with more than one floor, raising the foundation of the house, creating special flood barriers, and adapting valuables. This adaptation is in the Medium category, namely 60.70%. Social adaptation is environmental maintenance, knowledge of flood signs, preparedness and self-evacuation. Social adaptation, namely 74.73%, is in the High category and is the adaptation that has the most influence on research. Economic adaptation, namely making special savings such as registering for health insurance, is the lowest adaptation, namely 67.80% in the High category. This research provides important information regarding community adaptation measures to flood disasters in Barus District, which has the potential to increase community preparedness for flood disasters.